“Knowledge was clearly associated with education.” epistemic positioning in the context of informed choice: a scoping review and secondary qualitative analysis - Niamh Ireland-Blake; Fiona Cram; Kevin Dew; Sondra Bacharach; Jeanne Snelling; Peter Stone; Christina Buchanan; Sara Filoche (BMC Medical Ethics)
Abstract Background Being able to measure informed choice represents a mechanism for service evaluation to monitor whether informed choice is achieved in practice. Approaches to measuring informed choice to date have been based in the biomedical hegemony. Overlooked is the effect of epistemic positioning, that is, how people are positioned as credible knowers in relation to knowledge tested as being relevant for informed choice. Aims To identify and describe studies that have measured informed choice in the context of prenatal screening and to describe epistemic positioning of pregnant people in these studies. Methods Online databases to identify papers published from 2005 to 2021. The PRISMA-ScR checklist guided data collection, analysis and reporting. Secondary analysis that considered hermeneutics (e.g., knowledge that was tested, study design) and testimony (e.g., population descriptors) developed a priori. Findings Twenty-nine studies explored the measurement of informed choice. None reported that pregnant people were involved in the design of the study. Two studies reported pregnant people had some involvement in the design of the measurement. Knowledge tested for informed choice included technical aspects of screening, conditions screened and mathematical concepts. Twenty-seven studies attributed informed choice to population descriptors (e.g., race/ethnicity, age, education). Population descriptors were reified as characteristics of epistemic credibility for informed choice obtained. For example, when compared to a high school qualification, a tertiary qualification was a statistically significant characteristic of informed choice. When compared by race, white people were found to be significantly more likely to make an informed choice. Additional demographic descriptors such as age, language spoken, faith and previous pregnancies were used to further explain differences for informed choice obtained. Explanations about underlying assumptions of population descriptors were infrequent. Conclusion Using population descriptors in the biomedical hegemony as explanatory variables for informed choice can position (groups of) people as more, or less, epistemically credible. Such positioning could perpetuate epistemic injustices in practice leading to inequitable access to healthcare. To better uphold (pregnant) people as credible knowers population descriptors should instead be contextual (and contextualising) variables. For example, as indicators of social privilege. Further, making room for ways of knowing that go beyond the biomedical hegemony requires the development of epistemically just ‘measures’ through intentional, inclusive design.